Antenatal corticosteroids is associated with better postnatal growth outcomes of very preterm infants: A national multicenter cohort study in China - Li, Tianhao; Shen, Wei; Wu, Fan; Mao, Jian; Liu, Ling; Chang, Yanmei; Zhang, Rong; Ye, Xiuzhen; Qiu, Yinping; Ma, Li; Cheng, Rui; Wu, Hui; et al. (Frontiers in Pediatrics, 2023)
Introduction Antenatal corticosteroids (ACS) administration is a standardized prenatal care for accelerating fetal maturation before anticipated preterm delivery, however, its effect on nutrition and growth is yet uncertain. This study aimed to examine if ACS application is associated with improvement in postnatal growth and nutrition in very preterm infants (VPIs). Methods This was a secondary analysis of a multicenter prospective survey included infants born before 32 weeks gestation and admitted to 28 tertiary neonatal intensive care units throughout China from September 2019 to December 2020. Infants were divided into no ACS, partial ACS and complete ACS groups according to the steroids exposure. For infants exposed to antenatal corticosteroids, complete ACS was defined as receiving all doses of steroids 24 h-7 days before delivery, otherwise it was referred to partial ACS. The primary outcomes of postnatal growth were compared among the 3 groups. The multivariable regression analyses were applied to evaluate the association of different steroids coverage with postnatal growth and nutritional outcomes while adjusting for potential confounders. For each outcome, no ACS coverage was defined as the reference group. Data were presented as unstandardized coefficients or adjusted odds ratios with 95% confidence intervals, P < 0.05 (2-sided) indicated statistical significance. Results Among 2,514 infants included, complete ACS, partial ACS and no ACS group accounted for 48.7% (1,224/2,514), 29.2% (735/2,514) and 22.1% (555/2,514), respectively. The median weight growth velocity was 14.6 g/kg/d, 14.1 g/kg/d and 13.5 g/kg/d in complete, partial and no ACS group respectively with significant difference (P < 0.001). In multivariable analyses, both complete and partial ACS coverage were associated with shorter cumulative fasting time, faster weight growth velocity, less dramatic decline in Z-score of weight, and lower incidence of extrauterine growth restriction [aOR (95%CI): 0.603 (0.460, 0.789) and 0.636 (0.476,0.851), respectively] when compared with no ACS. Moreover, the faster length growth velocity and earlier enteral feeding start time were observed only in infants with complete ACS coverage. Conclusions Both complete and partial ACS are associated with better postnatal growth outcomes in very preterm infants. This efficacy appeared to be more obvious in infants exposed to complete ACS.